Design, Molecular Docking, and Pharmacokinetic Evaluation of 4-Aminoantipyrine Derivatives as Potential Anticancer Compounds Targeting Histone Deacetylase-2 (HDAC-2) - Abdullah, Doaa; Hamzah, Mohammed Jasim; Alwash, Ameer H. (Journal of Pharmacology and Drug Development, 2026)
Objective: Histone deacetylase-2 (HDAC-2) has emerged as an important molecular target in cancer therapy because of its role in gene silencing, regulation of the cell cycle, and resistance to apoptosis in several cancer types. In the present study, a series of novel 4-aminoantipyrine-based derivatives incorporating semicarbazide, thiosemicarbazide, and hydroxylamine pharmacophoric groups were rationally designed and evaluated for their potential HDAC-2 inhibitory activity using in silico approaches. Methods:. The binding affinity of the newly designed compounds toward the HDAC-2 enzyme and their interactions within the catalytic pocket were investigated using molecular docking analysis. The three-dimensional structure of HDAC-2 (PDB ID: 4LXZ) was obtained from the RCSB Protein Data Bank and prepared for docking studies. Results: Docking indicated that ligand stability within the enzyme active site was mainly achieved through coordination with the catalytic zinc ion, in addition to hydrogen bonding and hydrophobic interactions with essential amino acid residues located in the HDAC-2 catalytic domain. The reference inhibitor vorinostat (SAHA) was used as a standard compound and produced a docking score of −5.445 kcal/mol. Among the designed compounds, Compound Ia exhibited the most favorable binding energy with a calculated ΔG of −9.711 kcal/mol. In addition, Compound IIe and Compound Ib demonstrated promising docking scores of −8.285 and −8.147 kcal/mol, respectively. Conclusions: Pharmacokinetic properties were predicted using the QikProp module, revealing that most designed compounds exhibited acceptable drug-likeness according to Lipinski’s Rule of Five. These computational findings suggest that the designed derivatives may represent promising candidates as HDAC-2 inhibitors with potential anticancer activity.